Effect of Reactive Power Capability of the PV Inverter on the Power System Quality - Raghad Adeeb Othman; Omar Sharaf Al-Deen Al-Yozbaky (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Distributed generation (DG) based on a photovoltaic system (PV) connected to a power system is a very promising solution to meet the present demand for energy and to reap the advantages of using clean energy. With the exponential increase in the deployment of distributed energy sources based on renewable energy, the reactive power drawn from the grid has increased dramatically compared to the active power. This affects the quality of the power from the network. Reactive power is usually required to regulate the power factor and the grid voltage so as to improve the ability of the system to handle power. In this paper, the reactive power capacity of a PV inverter connected to the grid was determined using the MATLAB/Simulink program. The power (active and reactive) injected into the network were independently controlled by their reference values. A study was conducted on the effects of the injection/absorption of reactive power on the quality of power under different operating conditions.